Analisis Desain Visual Branding Kafe “Literacy Coffee” - Fauzie, Muhammad Indra (Universitas Muhammadiyah Sumatera Utara, 2023)
In this era of modernization, many business people have set up business premises such as cafes with designs that uphold high aesthetic values and also have a luxurious impression to attract the interest of consumers who see them. This is different from